\(-x^2-2x+15=-\left(x^2+2x-15\right)\)
\(=-\left[\left(x^2-3x\right)+\left(5x-15\right)\right]\)
\(=-\left[x\left(x-3\right)+5\left(x-3\right)\right]\)
\(=-\left(x-3\right)\left(x+5\right)\)
Ta có: -x^2-2x+15 = -x^2-5x+3x+15 = -x(x+5)+3(x+5) = (3-x)(x+5).
Hok tốt ~~~
-x2 - 2x + 15
= -x2 + 3x - 5x + 15
= ( 3x - x2 ) + ( 15 - 5x )
= x( 3 - x ) + 5( 3 - x )
= ( 3 - x )( x + 5 )
\(-x^2-2x+15\)
\(=-x^2-5x+3x+15\)
\(=-x\left(x+5\right)+3\left(x+5\right)\)
\(=\left(3-x\right)\left(x+5\right)\)
Bài làm :
Ta có :
-x2 - 2x + 15
= -x2 + 3x - 5x + 15
= ( 3x - x2 ) + ( 15 - 5x )
= x( 3 - x ) + 5( 3 - x )
= ( 3 - x )( x + 5 )
\(-x^2-2x+15\)
\(=-x^2+3x-5x+15\)
\(=\left(3x-x^2\right)-\left(5x+15\right)\)
\(=x\left(3-x\right)-5\left(x-3\right)\)
\(=x\left(3-x\right)+5\left(3-x\right)\)
\(=\left(3-x\right)\left(x+5\right)\)